1983
DOI: 10.1021/j100227a019
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of compounds adsorbed into cellulose. 1. Decay of excited tris(2,2'-bipyridine)ruthenium(II)

Abstract: for transfer of even as much as 0.1 electron, large shifts in frequency should not occur. Quite a bit of charge clearly can be added, or removed, or redistributed in the porphyrin without large accompanying changes in vibrational frequencies. Therefore, the energetics of ligand binding and oxidation and reduction may be influenced significantly by charge-transfer interactions without producing frequency shifts in the Raman spectra that are detectable with conventional Raman equipment.Additional evidence for sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 9 publications
6
35
0
Order By: Relevance
“…It has been observed that when incorporated probe concentrations reach a critical value, the probes suffer from concentration quenching and triplet state annihilation. [46] This could explain the different photobleaching behaviors observed for S1 and S2. Although the probe concentration in S1 is lower than S2, poor solubility of the probe in PDMS matrix could cause local probe aggregation to accelerate photobleaching.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that when incorporated probe concentrations reach a critical value, the probes suffer from concentration quenching and triplet state annihilation. [46] This could explain the different photobleaching behaviors observed for S1 and S2. Although the probe concentration in S1 is lower than S2, poor solubility of the probe in PDMS matrix could cause local probe aggregation to accelerate photobleaching.…”
Section: Resultsmentioning
confidence: 99%
“…There are many examples of such reactions, based usually on the observation of the quenching of the luminescence of a light-absorbing species by an e.t. partner co-dissolved in a rigid glass [62] or polymer matrix [63]; Table 2 lists some representative example. This type of static quenching requires relatively high quencher concentrations and it follows the Perrin "action sphere" model [64].…”
Section: Electron Transfer In Polar Glasses 1611mentioning
confidence: 99%
“…A linear SV plot for a host-guest solid material, which generally indicates homogeneous spatial distribution with only static or only dynamic quenching, is difficult to be achieved because the structural and surface homogeneity of the host materials, the optimization of the hostguest interactions and the guest-guest interactions are required. Table 3 lists some reported [Ru(bpy) 3 ] 2+ immobilized heterogeneous systems and the K sv values for [Ru(bpy) 3 ] 2+ self-quenching [17,[34][35][36][37][38][39]. In [Ru(bpy) 3 ] 2+ -zeolite Y system, the complex was confined in a cage to prohibit intermolecular contact of the complex, therefore, self-quenching can occur only when the complexes are confined in the adjacent cage (static self-quenching is thought to be dominant).…”
Section: Luminescence Of [Ru(bpy) 3 ] 2+ Adsorbed On Al-mpssmentioning
confidence: 99%
“…The self-quenching process of [Ru(bpy) 3 ] 2+ as a function of the loading amount indicates that the average distance between adjacent [Ru(bpy) 3 ] 2+ is controllable by changing the loading amount of the [Ru(bpy) 3 ] 2+ . From the Quasi SV plots for the present Al-MPS systems, where the plots are linear in all the concentration examined in the present study (the maximum value is 0.10 mol L À1 (0.058 mmol g À1 ) for Al-MPS-12 and 0.14 mol L À1 (0.059 mmol g À1 ) for Al-MPS-16 (the concentrations [34,35] and the lifetime [10]). In comparison to the aqueous solution, the Al-MPS systems showed higher K sv values (190 or 160 L mol À1 for Al-MPS-16 and Al-MPS-12, respectively).…”
Section: Luminescence Of [Ru(bpy) 3 ] 2+ Adsorbed On Al-mpssmentioning
confidence: 99%